Building exposure model for seismic risk assessment of the city of Strumica - Angova-Kolevska Nadica; Vitanova Marija (Građevinski Materijali i Konstrukcije)
Seismic risk assessment at the city scale has always been useful for pre-earthquake planning, managing future investments, and prioritizing the seismic repair and retrofit of existing buildings immediately after the earthquake. It is carried out by combining hazard, exposure, and vulnerability models. Exposure in this context, refers to the elements at risk: population, buildings, lifeline systems, or socioeconomic activities. Risk assessment analysis for different regions and cities worldwide shows that exposure and vulnerability are key elements for effective risk assessment. This paper provides an inside into the development of an exposure model of Strumica, North Macedonia, that describes the distribution of Strumica's main residential, industrial, and commercial building classes. The exposure database consisting of the existing building inventory is created using the international standard taxonomy for earthquake risk assessment, proposed by the Global Earthquake Model. This exposure model points out problems and concerns brought about by the implementation process and details the practical solutions and strategies used to achieve the set goals. The long-term expectation is that this exposure model will allow updating existing plans for emergencies, crises, and disasters, allowing city planners to include seismic risk assessment analyses that contain real data to encourage future risk reduction strategies.